Factors Affecting Unemployment In Maluku Province - Saptenno, Fibryano; Amin, Amin; Sangur, Korneles; Liur, Lisye Magdalena (Jurnal Ekonomi, 2024)
The research objective is to determine the effectiveness of fiscal and monetary policies in overcoming the problem of unemployment in Maluku Province. The research method used is quantitative research, using time series secondary data with a data range from 2011-2023. The research data consists of Maluku Province government expenditure data, BI Rate data, and Maluku Province Open Unemployment Rate (TPT) data. Data comes from the official website of the Indonesian Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia (Djpk Kemenkue), the analysis tool uses multiple regression, data is obtained with the help of the Eviews 12 application. The research results partially show the influence of fiscal policy variables on the unemployment variable has a negative regression coefficient with prob. t-statistic is less than α 5%, while the influence of the monetary policy variable on the unemployment variable has a positive regression coefficient with prob. t-statistic is greater than α 5%, simultaneously the fiscal and monetary policy variables on unemployment have prob. f-statistic is smaller than α 5%. Research conclusions (1) fiscal policy has a significant effect on reducing the unemployment rate, (2) monetary policy has an insignificant effect on increasing the unemployment rate, (3) fiscal and monetary policy together have an effect on the unemployment rate in Maluku Province .